Peran Esensial Keluarga Penderita Hipertensi - Ulfah Agus Sukrillah; Herry Prasetyo; Walin Walin (JURNAL KEPERAWATAN MERSI, 2021)
Background: Hypertension disease still  occupies the    largest  proportion  of  infectious  diseases carried out  as much   as  64.83%  while  the  second  most  is  diabetes  mellitus  by  19.2%. Both  diseases  are the top priorities  for  non-communicable  disease    control in Indonesia and the  world. Please be  aware that  the family  relationship of the closest  person  such as  family  is a good  support  for  people with  any  disease  as  well as hypertension disease.Methods:  The subject of the study  is people with  hypertension. Type of  journal that is original article  instead  of  review  of research  theme of family  support  journal  content  in  people with  hypertension Type of  research  that is  quantitative data collection of article selection  process is determined  in accordance  with  inclusion criteria.  The  data  collection process uses  the extraction method.The Result:  the prevalence of hypertension  that  occurs more  in  women  after the age  of  45 to 55  years  is  due to the production of estrogen hormones  that  gradually  decrease  naturally    with  age. The level of  education  of respondents  is known to be mostly    basic education.Conclusion:  firstly the characteristics of the elderly  mostly    have  the age of the elderly  category  have a female  gender  and  have a  basic education.  The  second  one treats  patients   modifying the   environment  and  utilizing  health  facilities  positive  effects  of  family  support  for  people with  hypertension.